Potential pharmacokinetic and pharmacodynamic herb-drug interactions of Andrographis paniculata (Burm. f.) and andrographolide: A systematic review - Elza Sundhani; Endang Lukitaningsih; Arief Nurrochmad; Agung Endro Nugroho (Shahrekord University of Medical Sciences, 2022)
Introduction: Herb-drug interactions (HDIs) in pharmacokinetics and pharmacodynamics can occur when natural compounds are used in combination with drugs. This study aimed to review the potential interaction of Andrographis paniculata (Burm. f.) extract (APE) and its primary compound andrographolide (AND) with several drugs exhibiting various pharmacological activities.Methods: In this systematic review, articles were collected from international databases such as PubMed, Science Direct, Springer Link, and Scopus until August 2021. The following keywords were used: Andrographis paniculata, andrographolide, HDI, drug interaction, pharmacokinetics, and pharmacology. This review was written in accordance with the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA), SYRCLE's risk of bias (RoB) tool for animal intervention studies, and Cochrane RoB 2 tool to analyze the RoB for qualitative assessment.Results: Twelve articles were included in accordance with the inclusion and exclusion criteria of this study. Five studies explored the potential of HDIs for combining APE with drugs and AND with theophylline, etoricoxib, nabumetone, naproxen, and tolbutamide. Five studies focused on AND in combination with aminophylline and doxofylline, meloxicam, glyburide, glimepiride, metformin, and warfarin. Two studies tested the combination of APE with gliclazide and midazolam. The HDI mechanism involving the inhibition or induction of cytochrome P450 enzyme expression was dominant in influencing the drug's pharmacokinetic profile. Pharmacological studies on the combination of several drugs, particularly anti-inflammatory and antidiabetic drugs, showed a synergistic activity.Conclusion: APE and AND have potential pharmacokinetic and pharmacodynamic HDIs with various drugs. This study can be used as a therapeutic consideration in clinical aspects related to the possibility of HDIs of A. paniculata (Burm. f.).